PENGEMBANGAN MODUL FILSAFAT BAHASA - Suryanto, Sugeng; Hendriyanto, Agoes (Universitas Pendidikan Indonesia, 2017)
This study aims to develop modules of course on the Language Philosophy in STKIP PGRI Pacitan. It held in the first year of 2013/2014 and the second year of 2015/2016. There are 3 phases of the development: problem identification, potential problems, and design of language philosophy modules. The result of the development in the first year are a module design of scientific language philosophy based on character values of Â Vol 1 and 2